Trends in vaccination schedules and up-to-date status of children 19–35 months, United States, 2015–2020. Issue 2 (9th January 2023) - Nguyen, Kimberly H.; Zhao, Ruitong; Mullins, Corey; Corlin, Laura; Beninger, Paul; Bednarczyk, Robert A.
Highlights: Adherence to the recommended schedule significantly increased from 2015 to 2020. Children following an alternative schedule decreased from 21.6% to 16.2%. There was no change in percentage of children receiving zero vaccinations. Children whose parents had lower incomes were more likely to not be up-to-date. Adherence to timely vaccinations ranged from 63.0% (Region 2) to 78.5% (Region 1). Abstract: Objectives: To estimate trends in, and factors associated with, vaccination patterns and up-to-date immunization status of U.S. children by 19 to 35 months of age. Methods: Data from the 2015 to 2020 National Immunization Surveys were used to assess trends in vaccination patterns, up-to-date status, and zero vaccination status of U.S. children by 19–35 months. Vaccination patterns were categorized as: 1) recommended, 2) alternate, or 3) unknown or unclassifiable. Multivariable analyses were conducted to examine factors associated with each vaccination pattern and up-to-date status for all recommended vaccines. Results: From 2015 to 2020, the proportion of U.S. children completing the recommended schedule increased from 62.5% to 69.4%, alternative schedule decreased from 21.6% to 16.2%, and unknown or unclassifiable schedules decreased from 15.9% to 14.3%. In addition, being not up-to-date decreased from 39.7% to 35.6%. There was no change in the percentage of children receiving zero vaccinations from 2015 to 2020 (0.9% to 0.9%). Respondents with lower household income or who were uninsured were more likely to follow an alternate or unknown/unclassifiable schedule, or not be up-to-date with vaccines. Conclusion: Following any schedule other than the recommended schedule was associated with not being up-to-date on immunizations. Increased efforts to catch up on recommended vaccines is important for protecting children's health. Further efforts should be made to improve timely adherence to recommended vaccination schedules, particularly among populations with the largest disparities in coverage through a tailored approach to increase confidence in and access to vaccines.